Changes in Clinical Practice amongst Nepalese Otolaryngologists during COVID-19 Pandemic - Tripathi, P.; Gurung, U.; Baidya, S.; Thapa, N. (Kathmandu University Medical Journal, 2022)
Background COVID-19 pandemic changed clinical practices more so for otolaryngologists due to inevitable risk of exposure.Objective To assess the changes in the clinical practice among Nepalese otolaryngologists during this pandemic.Method It was an observational study conducted as an online survey in the first two weeks of December 2020. A questionnaire pertaining to changes in clinical practice was mailed to 190 registered otolaryngologists working in various provinces of Nepal. Data were entered in Microsoft Excel 2007 and analysed in percentages.Result Out of the 77 (40.5%) who responded, nearly 50% resumed clinical practice after a month of national lockdown restarting everyday consultation by 64.9% mostly in hospital setting (81.8%) after screening patients via fever clinic by 87%. Modifications in clinical examinations was mostly done for neck (85.7%), oral cavity (44.2%) and nose (29.8%) examination with least with for ear examination (3.9%) Regular endoscopic evaluation was avoided by 19.4%. Only around 57% used adequate personal protective equipment. There was 93.5% reduction in elective operations. Mandatory COVID test was done by 89.6% mostly with reverse transcriptase polymerase chain reaction (95.9%) prior to semi-urgent case.Conclusion Changes in clinical practice were adapted to mitigate viral transmission. The changes were evident in the outpatient department where most patients were screened for fever and modifications made in the clinical examinations. Personal protective equipments were worn when available. Operative lists were limited to semi-urgent and urgent cases with covid testing customarily done for semi-urgent cases.